IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT IN DEVELOPING SANTRI CHARACTERS - Mukhtar Mukhtar; Hidayat Hidayat; Siti Mariah Ulfah (International Journal of Southeast Asia, 2020)
This article describes the implementation of Total Quality Management in developing students' characteristics, focusing on the problem of meeting the national education quality standards in order to improve the quality of management in developing the character of students. This study seeks to determine the implementation of TQM in developing the character of students in Islamic boarding schools, namely Pondok Pesantren PMDG Campus 10 Tanjung Jabung Timur, Talwah Al-Munawwaroh Merangin Regency and PKP Al-Hidayah Jambi City, by applying TQM standards to achieve organizational goals. Using a qualitative research approach with descriptive analysis, research results and conclusions that the pesantren is an educational institution that implements character education in an integrated manner throughout the whole process of education and learning. By implementing Total Quality management optimally by applying the management methodology of W. Edward Deming, Plan do check and Action that focus on customers, optimization of leadership roles, involving all employees / staff on quality and mutual commitment and continuous improvement will be able to develop the character of Santri. in accordance with the expectations of stakeholders so that a distinctive pesantren culture will be formed which distinguishes it from the education system outside the pesantren which is ready to face the times in the era of revolution 4.0.